The Impact of Strengthening Agricultural Extension Services : Evidence from Ethiopia - Buehren, Niklas; Goldstein, Markus; Molina, Ezequiel; Vaillant, Julia (World Bank, Washington, DC, 2017)
This paper evaluates the effect of the Rural Capacity Building Project, which aimed at promoting growth by strengthening the agricultural service systems in Ethiopia and by making them more responsive to smallholders' needs. The project intended to increase the outreach of agricultural extension services to help farmers become aware of and adopt economically viable and environmentally sustainable technologies and practices. The paper examines the impact of the Rural Capacity Building Project using panel data on 1,485 geographically dispersed households in project and control kebeles. The results show that the strengthening of extension services had a positive impact on economic participation in the household, land area cultivated, and adoption of marketable crops, suggesting that access to extension helped farmers switch to more commercial, market-oriented agriculture. In addition, and contrary to previous evidence from other countries, female-headed households seem to have benefited equally from the project. However, the project was not able to reduce the preexisting gender gap in agricultural outcomes.